Hardware development of reflection mode ultrasonic tomography system for monitoring flaws on pipeline - Nordin, Norsuhadat (Penerbit UTM Press, 2015)
The pipeline inspection is a key requirement to maintain structural health and pipeline integrity for oil and gas transportation over countries. Pipe failure is a critical problem that needs to be endured within the operational work. The defects or flaws existence on pipeline surface is one of the most leading factors to pipe failures. A new approach of non-destructive technique is implemented to monitor flaws on pipeline by using reflection-mode ultrasonic tomography system. This paper details on the hardware development of ultrasonic tomography system based on reflection mode detection. The system consists of ultrasonic transceiver sensors mounted circularly and contactless to the pipe surface. The modeling work described the ultrasonic ring configuration, ultrasonic signal behavior, sensors arrangement and image grid estimation. The developed instrumentation system is used to detect external and internal flaws on pipe surface. The results show that the reflection-mode ultrasonic tomography is capable to differentiate flaws detected based on the calculated depth verified from the distance measured and through the reconstructed image.